OPTIMALISASI PEMBELAJARAN NAḤWU MELALUI METODE TAQRAR DALAM MENINGKATKAN PEMAHAMAN SANTRI - Bahiroh, Zahrotun; Huda, Moh. Nurul; ‘Aisy, Raaghibah Rihaadatul; Maula, Fina Fairuzatul (Al-Fakkaar, 2025)
The taqrar method, a repetition technique known since the time of the Prophet Muhammad SAW, has been adopted in the teaching of naḥwu at Pondok Pesantren Al Utsmani Gejlig, Kajen, to improve students' understanding. This study aims to describe the implementation of the taqrar method in enhancing students' comprehension of naḥwu material and to evaluate its effectiveness. The approach used in this study is qualitative with a case study method. Data were collected through interviews, observations, and documentation from teachers and students, which were then validated using source triangulation. Data analysis was performed through data presentation, data condensation, and drawing conclusions. The results indicate that the implementation of the taqrar method at Pondok Pesantren Al Utsmani occurs in three stages: planning, implementation, and evaluation. The implementation of this method has proven effective in helping students memorize and understand naḥwu material, as expressed by both teachers and students. However, a weakness was identified, which is the tendency of students to feel sleepy during the application of this method. Based on these findings, it is recommended that teachers vary the implementation schedule to improve the effectiveness of the taqrar method.